Attribution and contestation: Relations between elites and other social groups. (September 2018) - Salverda, Tijo; Skovgaard-Smith, Irene
In this article, we explore the often ambiguous relations between elites and other social groups, both subordinate and of relatively equal standing. The article draws on two distinctive ethnographic cases: the white Franco-Mauritian elite, and the expert elite of management consultants in a Western European context. Our analysis of the two cases provides insights into how the power and status of elites are both contested and attributed by the people they interact with and relate to in concrete, yet substantially different contexts and situations. The aim is to show how the position and power of different kinds of elites are relationally negotiated and achieved. As we argue, a better understanding of the role of other social groups in the attribution, maintenance and contestation of status is relevant for understanding both more traditional economic elites and expert elites without tight networks.